Ionic liquids: a brief history - Welton, Tom (Biophysical reviews, 2018)
There is no doubt that ionic liquids have become a major subject of study for modern chemistry. We have become used to ever more publications in the field each year, although there is some evidence that this is beginning to plateau at approximately 3500 papers each year. They have been the subject of several major reviews and books, dealing with different applications and aspects of their behaviours. In this article, I will show a little of how interest in ionic liquids grew and developed.